Impact of co-application of biomethanated spent wash with bio-char on soil micronutrients and crop growth - Rohan Satish Oak; D.D Sarode; J.B Joshi; S. A Chavan (Journal of Sugarcane Research, 2021)
Biomethanated spentwash (BMS) and biochar are novel soil conditioners considered as value addition to the bi-products from agro-industry. The high nutrient content and organic matter of BMS and high retention of nutrient and organic carbon on biochar has potential of benefits for co-application. We studied the effect of BMS, biochar and their co-application on soybean, which is a common rotation crop in Sugarcane. A field experiment was conducted in randomized block design in vertisols. BMS was produced at Ugar sugar works ltd. and biochar from agriculture waste. Treatments comprised of BMS application@ 60, 66 and 72 m3 ha-1, as sole amendment and in combination with biochar @ 2.5 t ha-1. Post-harvest soil analysis demonstrated a non-significant effect of treatments on soil pH, electrical conductivity and micro-nutrients. However, available Zn, Fe and Mn were numerically increased for all BMS treatments. BMS and biochar or their co-application had no significant effect on germination and plant height of soybean. However the number of soybean pods and grain yield was significantly improved. Grain yield of soybean in BMS 60 m3 ha-1 plus biochar co-applied treatment was significantly higher than all other treatments. Grain yield of BMS 66 m3 ha-1 and other BMS plus BC treatments were at par with each other and significantly higher than sole biochar 2.5 t ha-1, RDF and control.